The Effects of Expiratory Rib Cage Compression before Endotracheal Suctioning on Arterial Blood Gases in Patients Under Mechanical Ventilation - M. Kohan; A. Najaf Yarandi; H. Peyrovi; F. Hoseini (Iran University of Medical Sciences, 2007)
Background & Aim : Endotracheal suctioning is one of the most frequently used methods for airway clearance in patients under mechanical ventilation. Chest physiotherapy techniques such as expiratory rib cage compression before endotracheal suctioning can be used as a means to facilitate mobilizing and removing airway secretions and improving alveolar ventilation. This study was carried out to determine the effects of expiratory rib cage compression before endotracheal suctioning on arterial blood gases in patients mechanically ventilated patients.   Material & Method : This research was a clinical trial study with a crossover design. The subjects consisted of 70 (35 females, 35 males) mechanically ventilated patients who were admitted to medical and surgical intensive care units and emergency department of Hazrat-Rasool Hospital in Tehran. Subjects were selected with consecutive sampling. The patients received endotracheal suctioning with and without rib cage compression, with a minimum 3-hours interval between the two interventions. Expiratory rib cage compression was performed for 5 minutes before endotracheal suctioning. Arterial blood gases were measured 5 minutes before and 25 minutes after endotracheal suctioning. Data were recorded on the data recording sheet. Data were analyzed using Wilcoxon and paired t-tests.   Results: There were a statistically significant differences in the ratio of arterial partial pressure of oxygen to fraction of inspired oxygen (Pao2/Fio2), Paco2, and arterial oxygen saturation (Sao2) between before and after endotracheal suctioning in both methods (endotracheal suctioning with and without rib cage compression) (p=0.000). Moreover, there were statistically significant differences in the ratio of arterial partial pressure of oxygen to fraction of inspired oxygen (P=0.000), Paco2 (P=0.048), and arterial oxygen saturation (P=0.000) between the two methods.   Conclusion: Findings showed that expiratory rib cage compression before endotracheal suctioning improves arterial blood gases exchanges in patients under mechanical ventilation, so, performing expiratory rib cage compression before endotracheal suctioning in these patients is recommended.